Effect of the Early Administration of Selective Serotonin Reuptake Inhibitors on the Time Course of Poststroke Fatigue: A 2-Year Longitudinal Study - Wang, Jinjing; Wang, Fang; Gu, Mengmeng; Xiao, Lulu; Xu, Pengfei; Guo, Jianglong; Jiang, Shiyi; Liu, Yujing; Liu, Yuanlu; Sun, Wen; Liu, Xinfeng (Frontiers in Neurology, 2022)
Background: Poststroke fatigue (PSF) is a dynamic process over time. Current evidence for interventions for PSF is limited. Our study investigated the effects of selective serotonin reuptake inhibitors (SSRIs) on the time course of PSF. Methods: The patients with acute ischaemic stroke were enrolled in this study. All patients were scored with the Fatigue Severity Scale (FSS) at baseline and 6, 12, and 24 months after the index stroke. The time course of PSF was classified as non-PSF, incident PSF, recovered PSF and persistent PSF according to the PSF status at baseline and the 24-month follow-up. Multivariate logistic regression analysis and generalized mixed model were applied to explore the relationships between SSRIs and the time course of PSF. Results: Eight hundred forty-seven patients were analysed in this study. No significant association between SSRIs and the time course of PSF was observed in all patients (p=0.076). The subgroup analyses indicated that SSRI antidepressants reduced the risk of incident PSF (Odds Ratio [OR] 0.23; 95% conﬁdence interval [CI] 0.05-0.96, p=0.044) and persistent PSF (OR 0.28; 95% CI 0.09-0.90, p=0.033) in the PSD subgroup, but not in the non-PSD group. In the longitudinal analysis, generalized logistical mixed-effect models indicated that early administration of SSRIs reduced the risk (OR 0.955; 95% CI 0.928-0.984) and severity (β=-0.02, p=0.045) of PSF in the PSD subgroup. Conclusion: No relationship was identified between the use of SSRIs and the time course of PSF in all patients. However, these drugs might be effective in PSF patients with depression.